A Riemann-Hilbert Approach to the Multicomponent Kaup-Newell Equation - Jian-bing Zhang; Ze-xuan Zhang (Advances in Mathematical Physics)
A Riemann-Hilbert approach is developed to the multicomponent Kaup-Newell equation. The formula is presented of N-soliton solutions through an identity jump matrix related to the inverse scattering problems with reflectionless potential.